The Author’s Worldview in Jack London’s The Call of The Wild - Nasrum, Nasrum; Faiqah, Afifah (Journal of Islamic Culture and Literature (JICeL), 2020)
This research discusses about the genetic structuralism in Jack London’s The Call of the Wild which aims to find the way of author’s world view. This research is based on Lucien Goldmann’s theory of genetic structuralism which not only referres to intrinsic elements but also it discusses about the extrinsic elements. The research applied qualitative method. The researchers used note taking as the instrument to reveal the valid data. The findings show that the author talked about the cruelty competition of capitalism as a worker. The researchers found all of the elements of worldview namely 1) God, 2) Science, 3) Reality, 4) Self, 5) Ethics, and 6) Society in the Novel. The researchers conclude that the author described the social conditions of society that cannot be separated from his hard life journey. Keywords: World View, Genetic Structuralism, Human Facts, Literary Work Abstrak Penelitian ini membahas tentang strukturalisme genetik dalam The Call of the Wild Novel karya Jack London yang bertujuan untuk mengetahui cara pandang penulis terhadap dunia. Penelitian ini didasarkan pada teori strukturalisme genetik Lucien Goldmann yang tidak hanya mengacu pada unsur intrinsik tetapi juga membahas tentang unsur ekstrinsik. Metode penelitian yang digunakan adalah metode kualitatif. Peneliti menggunakan pencatatan sebagai instrumen untuk mengungkap data yang valid. Hasil penelitian menunjukkan bahwa penulis berbicara tentang persaingan kejam kapitalisme sebagai pekerja. Peneliti menemukan semua unsur pandangan dunia yaitu 1) Tuhan, 2) Sains, 3) Realitas, 4) Diri, 5) Etika, dan 6) Masyarakat dalam Novel. Peneliti menyimpulkan bahwa penulis menggambarkan kondisi sosial masyarakat yang tidak lepas dari perjalanan hidupnya yang keras. Kata Kunci: Pandangan Dunia, Strukturalisme Genetik, Fakta Manusia, Karya Sastra.